Growth and Production of Fusan FP4 Inulinase at 0.15% and 0.2% Yeast Extract Concentration - Nafisa, Arifa Rizqi; Wijanarka (Jurnal Biologi Tropis, 2025)
Inulin is a polysaccharide, consisting of fructose units. Inulin has several benefits for our own bodies and for industrial circles. Inulinase E.C.3.2.1.7. is a hydrolytic enzyme that catalyzes the hydrolysis reaction of inulin polysaccharides into fructose and/or fructooligosaccharides. This study aims to determine the growth rate of Fusan FP4 inulinnase and the production of Fusan FP4 inulinnase at yeast extract concentrations of 0.15% and 0.2%. Conversion of tubers into fructose with enzymatic techniques (inulinase enzyme) can produce 95% fructose. Fusan FP4 is a protoplast fusion of indigenous yeast Pichia manshurica. Yeast Extract is a source of Nitrogen for microorganisms in culture media. The concentration of Yeast Extract in the media can affect the growth and metabolic products of microorganisms. Inulinase activity was determined by measuring reducing sugars combined with inulin as a substrate. This activity was measured using a spectrophotometer at a wavelength of 520 nm. The study showed that the specific growth rate at a yeast extract concentration of 0.2% was higher than yeast extract concentration of 0.15%. However, The highest inulinase activity was found at a yeast extract concentration of 0.2%.